Assessment of medication adherence in patients with chronic diseases in Tabuk, Kingdom of Saudi Arabia - Kousalya Prabahar; Maymonah Abdullah Albalawi; Lama Almani; Sarah Alenizy (Wolters Kluwer Medknow Publications, 2020)
Objective: Uncontrolled chronic diseases such as hypertension and diabetes mellitus can lead to severe complications. Poor adherence to medication is one of the important reasons, leading to complications for chronically diseased patients. We aimed to assess the trend toward medication adherence and the reasons for medication nonadherence in chronic disease patients in Tabuk city in Saudi Arabia. Methods: A cross-sectional study was conducted at a tertiary care hospital in Tabuk, Saudi Arabia. Participants were selected and interviewed for information regarding their medication adherence. A medication adherence rating scale questionnaire was used to measure the level of adherence in study participants. The data were analyzed by the statistical package for the social sciences (SPSS) database 24. Findings: Overall, 208 participants were involved in this study. Among these, 134 (64.4%) were female, and 74 (35.6%) were male. This study showed that 159 (76.44%) participants were adherent to their medications and nearly one-quarter of patients were nonadherent to their medications. No statistically significant differences were found between male and female patients toward their medication adherence. The primary intentional and nonintentional reason for nonadherence was side effects and forgetfulness, respectively. Conclusion: Tailoring the therapy according to the individual need of the patients will maximize the patient's adherence toward medications.